OP0212 Phospholipid Transfer Protein (PLTP): A Link between Inflammation and Lipids in Rheumatoid Arthritis?. (15th July 2016) - Audo, R.; Deckert, V.; Daien, C.; Che, H.; Elhmioui, J.; Pais de Barros, J.-P.; Lemaire, S.; Desrumaux, C.; Hahne, M.; Combe, B.; Lagrost, L.; Morel, J.
Abstract : Background: Rheumatoid arthritis (RA) is associated with an increased risk of cardiovascular events related to inflammation. In early RA, there is an imbalance between inflammation and lipids. The LXR (Liver X receptors) pathway regulates lipid metabolism and inflammation and it was recently shown to be the most upregulated pathway in RA synovial fluid macrophages compared to blood monocytes (1). Plasma phospholipid transfer protein (PLTP) is one of the LXR's upregulated targets genes. PLTP has been shown to be involved in lipids metabolism, atherosclerosis and, more recently, in the inflammatory response. PLTP was alternatively described as a proinflammatory factor when expressed in cells or as an anti-inflammatory agent through its ability to bind and neutralize LPS. Objectives: We investigated PLTP expression in RA and its effects on synovial fibroblasts from RA (RAFLS). Methods: PLTP expression was examined in FLS from RA patients by qPCR, WB analysis and immunochemistry. ABCA1 expression was analysed by flow cytometry. The effect of recombinant human PLTP on IL-8, IL-6, VEGF and MMP3 production, and on cell proliferation was assessed by ELISA and 3 H-Thymidine incorporation, respectively. Inactivation of lipid transfer activity of PLTP was obtained by heating PLTP for 2 hours at 65°C. Lipid transfer activity of PLTP and pro-inflammatory cytokines were measured in synovial fluid (SF) from RA patients and controls (osteoarthritis (OA) patients). Results: PLTP mRNA was increased in RAFLS (n=11) compared to OAFLS (n=5) but not statistically significant (p=0.08) whereas PLTP protein levels were significantly higher in RAFLS (p=0.04). RA synovial tissues showed higher PLTP staining than OA. ABCA1, a putative receptor of PLTP, was found on RAFLS both at the cell surface and at the intracellular level (n=5). Native PLTP and heat-inactivated recPLTP were able to significantly increase the production of inflammatory cytokines (IL-6 and IL-8), of the VEGF angiogenic mediator and of the MMP3 metalloproteinase in RAFLS. PLTP and heat-inactivated PLTP also significantly increased RAFLS proliferation (by 3.3±.1.2 and 5.5±2.1 fold, respectively). These effects were markedly impaired after treatment with anti-PLTP antibodies or glyburide ( i.e. a chemical inhibitor of the ABCA-1 transporter). SF of RA patients were found to display elevated levels of PLTP activity compared to OA patients (p=0.0009). PLTP activity levels in RASF correlated with IL-6 and IL-1b (r=0.53, p=0.0086, and r=0.58, p=0.018, respectively), as well as with some lipid parameters. Conclusions: It is shown for the first time that PLTP is highly expressed in the joint of RA patients. It is able to directly trigger inflammation and FLS proliferation, independently of its lipids transfer activity. References: Asquith DL et al. ARD, 2013 Disclosure of Interest: None declared